Taxing artificial intelligence - Oberson, Xavier (Cheltenham Edward Elgar Publishing Limited, 2024)
"In this insightful book, a fully updated edition of the author's Taxing Robots, Xavier Oberson explores taxing Artificial Intelligence (AI) as a potential response to rising workplace disruption and inequality as the use of AI across the economy continues to grow. Drawing on key legal and economic principles, Xavier Oberson, who may be regarded as a pioneer of the idea of taxing robots, examines diverse tax models that could be applied to either the use of AI, such as a usage or automation tax, or to AI systems directly, and presents a novel argument in favour of taxing AI. Oberson highlights critical issues including definitions of AI and robots, the complexity of granting a tax capacity to AI, and the compatibility of AI taxes with international tax rules. In particular, this cutting-edge new edition analyses how VAT can be applied to enterprises using AI and autonomous AI systems, and reflects on the legal and technological limits facing lawmakers. Taxing Artificial Intelligence will be essential reading for scholars, policy makers and students across law and economics. It will also be invaluable for law and tax professionals seeking to understand the latest developments in AI, automation, and the future of work"--
Includes bibliographical references (pages 221-229) and index.
Keywords: Artificial intelligence -- Law and legislation; Artificial intelligence -- Taxation -- Law and legislation; Robots -- Taxation -- Law and legislation